Early growth of Zingiber zerumbet (L.) smith as affected by different organic fertilizers and harvesting times - Munawer, Nurhidah; Shahari, Rozilawati (Blue eyes Intelligence Engineering and Science Publication, 2019)
Zingiber zerumbet (L.) Smith or lempoyang has various application especially in pharmacological field. This study investigated the effects of different organic fertilizers andharvesting times on the early growth of lempoyang grown atPahang Matriculation College. The 9 treatment combinationswere arranged in a randomized complete block design with fivereplications. Chemical analysis of soil and organic fertilizerswere conducted. The morphological growth were regularlymeasured at 2 weeks interval. The interaction between organicfertilizers and harvesting times gave high significant (P≤0.001)effect to tiller and leaves number, plant height and pseudo-stemdiameter. Different organic fertilizers showed significantdifferences (p<0.05). Quail litter significantly produced thehighest mean on leaves number (14.94), tiller number (8.10),height (33.50) and pseudo-stem diameter (0.83). Mostmorphological attributes showed directly proportional to thetime. The maximum height (34.62) recorded in 150 days aftertransplanting (DAT) followed by 120 DAT (30.02). Combinationof goat manure with 150 DAT produced plants with the highest growth biometrics for leaves number, length of leaf 1, length ofleaf blade 1-3, width of leaf blade 1 and 2. From the findings ofthis study, it can be concluded that application of quail litter andgoat manure in combination with late harvest could enhanced thegrowth of lempoyang.